Eric Hobsbawm, sociologist of peasant millenarianism - Löwy, Michael (2018)
Thanks to the problematic of millenarianism, Eric Hobsbawm’s historiography incorporates all the richness of socio-cultural subjectivity - the depth of beliefs, feelings and emotions - into his analysis of historical events, which, from this viewpoint, are no longer perceived simply as products of the «objective» interplay of economic or political forces. Although he makes a careful distinction between primitive millenarianisms and modern revolutionary movements, Hobsbawm nevertheless shows their elective affinity between them. This does not mean that all revolutionary movements are millenarian in the strict sense or - which is even worse - that they are connected to a primitive type of chiliasm. All the same, the affinity between them is a basic fact in the history of peasant revolts against capitalist modernization. This is one of the most interesting research hypotheses outlined by Hobsbawm in his work of that period. He illustrated his idea in two fascinating case studies: rural anarchism in Andalusia and the Sicilian peasant leagues, both arising at the end of the nineteenth century and continuing into the twentieth.